Prion-Like Mechanisms in Parkinson’s Disease - Ma, Jiangnan; Gao, Jing; Wang, Jing; Xie, Anmu (Frontiers in Neuroscience, 2019)
Formation and aggregation of misfolded proteins in the central nervous system (CNS) is a key hallmark of several age-related neurodegenerative diseases, including Parkinson’s disease (PD), Alzheimer’s disease (AD), and amyotrophic lateral sclerosis (ALS). These diseases share key biophysical and biochemical characteristics with prion diseases. It is believed that PD is characterized by abnormal protein aggregation, mainly that of α-synuclein (α-syn). Of particular importance, there is growing evidence indicating that abnormal α-syn can spread to neighboring brain regions and cause aggregation of endogenous α-syn in these regions as seeds, in a “prion-like” manner. Abundant studies in vitro and in vivo have shown that α-syn goes through a templated conformational change, propagates from the original region to neighboring regions, and eventually cause neuron degeneration in the substantia nigra and striatum. The objective of this review is to summarize the mechanisms involved in the aggregation of abnormal intracellular α-syn and its subsequent cell-to-cell transmission. According to these findings, we look forward to effective therapeutic perspectives that can block the progression of neurodegenerative diseases.